(untitled) (Tempo e Argumento, 2024)
This article aims to analyse the construction of Afro-diasporic heritages between Nigeria and Brazil, showing how Yoruba history is reactivated in the cultural exchanges between the two sides of the Atlantic Ocean. We will see that in Nigeria today, the heritagization of monuments, cultural practices or natural sites has become a new weapon to reaffirm the supremacy of the main Yoruba traditional authorities. In these processes, "religion" occupies a central position in safeguarding Yoruba cultural traditions. But for Yoruba religion to become "heritage," it must first be thought of as "culture". The processes of selecting representations of Yoruba cultural heritage are thus activated on the shifting boundaries that separate religion and culture. Today, the role of the "diaspora" is crucial in recognising the heritage value of religious practices and monuments in Yoruba territory, building a transnational Afro-religious space.